2023
DOI: 10.1126/science.adg6006
|View full text |Cite
|
Sign up to set email alerts
|

Widespread shifts in body size within populations and assemblages

Inês S. Martins,
Franziska Schrodt,
Shane A. Blowes
et al.

Abstract: Biotic responses to global change include directional shifts in organismal traits. Body size, an integrative trait that determines demographic rates and ecosystem functions, is thought to be shrinking in the Anthropocene. Here, we assessed the prevalence of body size change in six taxon groups across 5025 assemblage time series spanning 1960 to 2020. Using the Price equation to partition this change into within-species body size versus compositional changes, we detected prevailing decreases in body size throug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 122 publications
1
1
0
Order By: Relevance
“…co-occurrence patterns), that were not taken into account in our study. Nevertheless, we show that the R 2 values we obtain are not random, and we report consistent results among occurrence, abundance and biomass models, among different levels of protection, and also similar to effects reported for other taxa such as birds (Barnes et al, 2022;Martins et al, 2023). We suggest that rarity and potential Allee effects cannot be ignored in the design and implementation of MPAs (White et al, 2021) since the persistence of rare predators, which contribute disproportionately to the IUCN Red List of extinction risk (Dulvy et al, 2014;Harnik et al, 2012), critically depend on them.…”
Section: Discussionsupporting
confidence: 90%
“…co-occurrence patterns), that were not taken into account in our study. Nevertheless, we show that the R 2 values we obtain are not random, and we report consistent results among occurrence, abundance and biomass models, among different levels of protection, and also similar to effects reported for other taxa such as birds (Barnes et al, 2022;Martins et al, 2023). We suggest that rarity and potential Allee effects cannot be ignored in the design and implementation of MPAs (White et al, 2021) since the persistence of rare predators, which contribute disproportionately to the IUCN Red List of extinction risk (Dulvy et al, 2014;Harnik et al, 2012), critically depend on them.…”
Section: Discussionsupporting
confidence: 90%
“…Such synchrony may also correspond to recently described global trends in the covariance of multiple ecosystem functions 39 , 88 . It could also be related to other widely reported patterns of ecological change, such as the global “community downsizing” of animal communities that occurs in response to both climate change and anthropogenic disturbance 89 , 90 and its impact on ecosystem functioning 91 , though further theoretical integration would also be required. When combined with these results, our findings highlight the potential for a new generation of whole ecosystem-level studies that go beyond the description of single trophic guild-level strategies to characterise communities, or single functions to characterise ecosystem responses.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more important are the global changes in fish that could lower their C15:0 content. When evaluating the body sizes of fish from 1960 to 2020, Martins et al found that the mean body sizes of fish have been decreasing [109]. This movement toward more smaller fish in the oceans, which may be due to combinations of overfishing and warmer temperature waters, are expected to result in fish that contain less fat, including C15:0.…”
Section: Drivers For Declining C15:0 Concentrationsmentioning
confidence: 99%